Parental Involvement in Children’s Remote Education: Examining the Case of the COVID-19 Pandemic - Olszewska-Gniadek, Joanna; Ostafińska-Molik, Barbara Paulina; Gaweł, Anna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
This paper presents the results of a study that aimed to determine how parents were involved in their children’s remote education during the SARS-CoV-2 pandemic, with comparisons at the beginning and at the end of the sanitary regime, and by parents’ education, place of residence, mode of work during the pandemic, number of children they had and the level of education of their child/children. The study was conducted by means of an online survey using two independent measurements: at the beginning of the pandemic and during the fifth wave of the pandemic. A sample of N = 75 respondents was surveyed in Measurement I, and N = 306 in Measurement II. A mixed survey procedure was used. The research tool was a self-administered survey questionnaire. The research found that the introduction of distance learning forced new arrangements for the organisation of home life, existing habits and interaction patterns, with parental involvement in their children’s distance education differentiated by parents’ socio-demographic characteristics. It was also found that recurrent periods of remote learning about the ongoing pandemic were increasingly burdensome for working parents, who did not see the benefits of this education for their children.